2009
DOI: 10.1161/circulationaha.109.855569
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Focus in an Accessory Left Atrial Appendage

Abstract: A 65-year-old man with symptomatic atrial fibrillation refractory to medical therapy was referred for repeat pulmonary vein (PV) isolation. Clinical symptoms included paroxysmal palpitations once to twice per week with associated light-headedness and chest pain. Initial PV isolation had been performed 6 months earlier without cessation of atrial fibrillation despite combined medical therapy with oral flecainide and bisoprolol. His past medical history was significant for hypertension, and in his family history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…The prevalence of accessory appendages in our investigation (28%) is in congruence with preceding studies which have shown prevalence between 10% -28% [6] [7] [9] [12] [21]. Moreover, accessory left atrial appendages have been implicated as the source of ectopy in patients with symptomatic atrial fibrillation refractory to medical treatment [16] [17]. Although some have contended the clinical significance of accessory appendages, describing these structures as anatomic variants as opposed to pathologic findings, the current analysis attempts to elucidate this question [6].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The prevalence of accessory appendages in our investigation (28%) is in congruence with preceding studies which have shown prevalence between 10% -28% [6] [7] [9] [12] [21]. Moreover, accessory left atrial appendages have been implicated as the source of ectopy in patients with symptomatic atrial fibrillation refractory to medical treatment [16] [17]. Although some have contended the clinical significance of accessory appendages, describing these structures as anatomic variants as opposed to pathologic findings, the current analysis attempts to elucidate this question [6].…”
Section: Discussionsupporting
confidence: 91%
“…Atrial fibrillation originating from the left atrium has been implicated in cerebrovascular accidents (CVA) and transient ischemic attacks (TIA) [14] [15]. Recently, ectopic fibrillatory activity and thrombus has been described in patients with accessory appendages and diverticula [10] [13] [16] [17]. Septal pouches, given their blind end morphology, have been implicated in case reports of thromboembolic disease as well as arrhythmia [5] [18]- [20].…”
Section: Introductionmentioning
confidence: 99%
“…Second, we could not reveal how the size of LA out-pouching structures affected the patients because most of the LA out-pouching structures detected in our study population were very small (less than 1cm) and the largest one measured just 1.2cm in diameter. In previous reports, the thrombogenic or arrhythmogenic potential of LA out-pouching structures were initially suggested in patient cases with large accessory LA appendages or diverticula [10,19,21]. Therefore, the effect of LA out-pouching structure size should be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…There are a few case reports describing that LADs and other accessory appendages are a potential source of thromboembolism and a potential cause of perforation risk during ablation [ 19 , 20 , 32 ]. Interestingly, histopathological analyses could demonstrate that LADs contain trabeculated myocardium which raises the hypothesis that LAD may be contractile and a source of ectopic activity, which was reported in a documented case report by Kileen et al [ 24 ]. However, the role of LADs in the pathomechanism of AF remains unclear.…”
Section: Discussionmentioning
confidence: 91%
“…They are reported to serve as an extra cardiac pacemaker focus, and comprise a risk factor for intracavitary thrombosis and cardiac perforation during ablation [ 19 23 ]. According to histopathological analyses, LADs contain trabeculated myocardium with the same wall structure as the surrounding myocardium and were firstly reported to show ectopic activity in a documented case report in 2009 [ 24 , 25 ]. Left sided septal pouches (LSSP) are considered structures that occur when the patent foramen ovale (PFO) is absent but the septum primum and septum secundum are not completely fused [ 26 ].…”
Section: Introductionmentioning
confidence: 99%